A STUDY OF THE EFFECT OF HUMAN SOUL ON EXTERNAL OBJECTS:: BETWEEN COPENHAGEN SCHOOL AND MULLA ṢADRA - Ali Arshad Riahi; Sayyed Mehran Tabatabaei; Mehdi Jafarzadeh (Sekolah Tinggi Agama Islam Sadra, 2015)
The theory of the effects of all human souls on external objects, from the viewpoint of Copenhagen School (in Quantum Physics), has made physicists deny the existence of two separate realms of the observer and the observed; they claim that causality is meaningless and profess that it is impossible to recognize the object. While, on the other hand, Mulla Ṣadra believes that the effect of soul on external objects is limited to the souls of prophets as well as saints and, barring evil eye or supplications, there is no such effect in others. In this article we argue that, based on Mulla Ṣadra’s teachings and philosophical doctrine, it is actually possible to generalize this effect to other human souls. Consequently, it is impossible to have an accurate recognition of the causes of events if causality is considered meaningless. In addition, it is feasible to have cognition about these causes of events through gnostic intuition.